Sport history - Gems, Gerald R., author.
1 online resource.
Keywords: This is a fundamental text for the study of sport history. It answers the why,' how,' and what' questions, introducing the key principles and practices of sport history and walking the reader through the fascinating stories, debates, issues, and national and international narratives that constitute the history of sport. The book provides an overview of the field and the various professional roles assumed by practitioners, such as researchers, academics, and public historians. It is brief, crisp, and to the point. The main general topics of interest within the field - gender, race, nationalism, religion, sport and leisure, and megaevents - are covered with introductory vignettes, stories of interest, a wide variety of theoretical frameworks, and relevant historiography in the most current and timely text of its kind. Each chapter provides a list of further readings for more in-depth study. Students are taught how to conduct research and present their findings in a variety of mediums, and teaching and publication tips are offered for educators. Sport History: The Basics is essential reading for any student on a sport-related degree course or with an interest in social and cultural history. It is also fascinating reading for anybody with a general interest in sport.